PENERAPAN PEMBELAJARAN BERBASIS MASALAH DALAM PEMBELAJARAN TEKS PUISI UNTUK SISWA KELAS VIII SMP NEGERI 4 SUNGAI PENUH - Yantama, Sulendari Putri; R.,, Syahrul; Afnita, Afnita (Universitas Negeri Padang, 2018)
ABSTRACTÂ This research is a qualitative descriptive study aimed (1) to describe the planning problem based learning model in learning to write text poetry class VIII SMP Negeri 4 Sungai Penuh; (2) describe the application of problem-based learning model in learning to write text poetry class VIII SMP Negeri 4 Sungai Penuh; (3) describe the describe evaluating problem based learning model in learning to write text poetry class VIII SMP Negeri 4 Sungai Penuh; (4) describe students opinions of problem-based learning model in learning to write text poetry class VIII SMP Negeri 4 Sungai Penuh. Subjects in this study were teachers in class VIII SMP Negeri 4 Sungai Penuh. The methods used to collect the data in this study is the method of documentation, observation and interview methods. The collected data were analyzed with descriptive methods. The results of this study are (1) planning problem based learning model created by teachers such as lesson plans matching with curriculum in 2013; (2) the application of problem-based learning model that teachers are in accordance with the syntax of problem-based learning model; (3) evaluating problem-based learning made by the teacher is in accordance with scientific assessment; (4) positive response of students towards problem-based learning in learning to write poetry texts of class VIII SMP Negeri 4 Sungai Penuh.Â Kata kunci : model pembelajaran berbasis masalah, puisi